Induction of MRSA Biofilm by Low-Dose β-Lactam Antibiotics: Specificity, Prevalence and Dose-Response Effects. Issue 1 (1st January 2014) - Ng, Mandy; Epstein, Samuel B.; Callahan, Mary T.; Piotrowski, Brian O.; Simon, Gary L.; Roberts, Afsoon D.; Keiser, John F.; Kaplan, Jeffrey B.
Methicillin-resistant Staphylococcus aureus (MRSA) is a leading cause of hospital- and community-associated infections. The formation of adherent clusters of cells known as biofilms is an important virulence factor in MRSA pathogenesis. Previous studies showed that subminimal inhibitory (sub-MIC) concentrations of methicillin induce biofilm formation in the community-associated MRSA strain LAC. In this study we measured the ability sub-MIC concentrations of eight other β-lactam antibiotics and six non-β-lactam antibiotics to induce LAC biofilm. All eight β-lactam antibiotics, but none of the non-β-lactam antibiotics, induced LAC biofilm. The dose-response effects of the eight β-lactam antibiotics on LAC biofilm varied from biphasic and bimodal to near-linear. We also found that sub-MIC methicillin induced biofilm in 33 out of 39 additional MRSA clinical isolates, which also exhibited biphasic, bimodal and linear dose-response curves. The amount of biofilm formation induced by sub-MIC methicillin was inversely proportional to the susceptibility of each strain to methicillin. Our results demonstrate that induction of biofilm by sub-MIC antibiotics is a common phenotype among MRSA clinical strains and is specific for β-lactam antibiotics. These findings may have relevance to the use of β-lactam antibiotics in clinical and agricultural settings.